Comparison of the Roche cobas® 4800 and Digene Hybrid Capture® 2 HPV tests for primary cervical cancer screening in the HPV FOCAL trial. Issue 1 (December 2015) - Cook, Darrel; Mei, Wendy; Smith, Laurie; van Niekerk, Dirk; Ceballos, Kathy; Franco, Eduardo; Coldman, Andrew; Ogilvie, Gina; Krajden, Mel
Abstract Background HPV FOCAL is a randomized trial (ISRCTN79347302, registered 20 Apr 2007) comparing high-risk (hr) HPV testing vs. liquid-based cytology (LBC) for cervical cancer screening of women aged 25–65. We compared the Digene Hybrid Capture® 2 High-Risk HPV DNA Test® (HC2) and the Roche cobas® 4800 HPV Test (COBAS) for primary screening. Methods Women (n  = 6, 172) were screened at baseline by HC2 and COBAS and by LBC 24 months later. We assessed HPV genotyping and reflex LBC for colposcopy triage of baseline HPV positive women. Results Overall HC2/COBAS agreement was 96.1 % (kappa 0.75) and positive agreement was 77.5 %. Baseline CIN2 and CIN3+ rates based on HPV screening were 8.6/1, 000 and 6.6/1, 000 respectively; 24 month rates were 0.7/1, 000 and 0.4/1, 000 (LBC screening). HC2 and COBAS were concordant positive for 91 % of round 1 CIN2 and 98 % of CIN3+. CIN3+ was significantly associated with HPV 16 (Odds Ratio [OR] 5.11; 95 % confidence interval [CI] 2.30, 11.37), but not HPV 18 (OR 2.62; 95 % CI 0.73, 9.49), vs. non-HPV 16/18 HPV at baseline. There was no significant association between HPV genotype and CIN2. CIN3+ was significantly more likely for high-grade (OR 5.99; 95 % CI 2.53, 14.18), but not low-grade (OR 0.54; 95 % CI 0.20, 1.49), vs. negative LBC. No significant association was observed between LBC grade and CIN2. HPV 16 and 18 were associated with 33 % of CIN2 and 68 % of CIN3+ identified at baseline. Conclusions For hrHPV positive women, abnormal reflex LBC is appropriate for colposcopy triage. In addition, immediate referral of women with HPV 16/18 and normal cytology may allow for earlier detection of CIN2+ lesions which would not be detected until after follow-up testing.